Decreased PECAM-1 May be a potential pathological factor for vascular injury in T2DM patients - Jun-Jun Xu; Han-Zhen Cai; Han Sun; Xiang Chen; Xia-Ming Cai (Scientific Reports)
Abstract Vascular injury is a common complication of type 2 diabetes mellitus (T2DM). Platelet endothelial cell adhesion molecule-1 (PECAM-1) is a vascular regulator. This study is to explore the possible pathological mechanism of PECAM-1 in vascular injury in T2DM. Plasma PECAM-1 was detected using ELISA in plasma samples of T2DMs and normal subjects. NetworkAnalyst was used to analyze the PECAM-1 transcript genes. PECAM-1 transcriptional gene variation in T2DM was analyzed from GSE26168 data from the GEO database. STRING line network database was used to obtain the proteins related to PECAM-1, and the ClusterProfiler package in R language was applied to perform PPI, GO and KEGG enrichment analysis. PECAM-1targeted drugs prediction was performed by Drugbank. Compared with 66 healthy controls, the plasma PECAM-1 levels in 66 patients with T2DM were significantly decreased (p < 0.001). Moreover, multivariate regression analysis indicated that PECAM-1 was an independent risk factor for vascular injury in T2DM patients. GSE26168 data of T2DM blood mRNA showed that the levels of the PECAM-1 gene transcription factors CREB3, GATAD1 and TEAD3 were significantly reduced, while CUX1 and RELA were significantly increased in T2DM patients. Functional enrichment analysis of PPI, GO and KEGG suggested that PECAM-1 was involved in regulation of vascular stability, endothelial function, and angiogenesis. DrugBank search revealed that fostamatinib is a targeted drug closely matching the PECAM-1 molecule. In patients with T2DM, the decrease in PECAM-1 is an independent risk factor for vascular injury. Abnormalities in PECAM-1 transcriptional factors are likely associated with the reduction in plasma PECAM-1 levels, which may be involved in the mechanism of vascular injury in T2DM. Fostamatinib may be a candidate drug for vascular injury in T2DMs.